Two-way Mirrors: Dancing in the Zoomosphere - Murphy, Siobhan (The International Journal of Screendance, 2021)
Dan Graham's work with mirrors and installation from the 1970s provides an unexpected launchpad for understanding the structures underlying perception in Zoom interfaces. The article explores the intricacies of Graham's two-way mirrors as a means to articulate perceptual experiences of dancing in the Zoomosphere, with examples from teaching, choreographing and performing via Zoom during Covid 19 isolation conditions.